Candelilla wax edible coating with Flourensia cernua bioactives to prolong the quality of tomato fruits - Ruiz-Martínez, Judith (2020)
The improvement of the postharvest quality of tomato fruits was evaluated using an edible coating functionalized with an Flourensia cernua extract evaluating the antifungal, structural, barrier, and optical properties. The formulation and evaluation of an edible coating and its application on tomato was evaluated using a response surface methodology to determine the ideal concentrations of candelilla wax, whey protein, and glycerol. Edible films showed good barrier properties, with water vapor permeability varying from 0.4350.404 g mm/m2 day kPa. The addition o F. cernua extract showed significant improvement in the transparency of films. The edible coating applied to tomato reduced weight and firmness loss. The sensory evaluation proved that the product obtained is acceptable for consumers. The edible coating added with F. cernua extract was the most effective in inhibiting the growth of pathogenic fungi and the visual appearance at the end of storage confirmed the beneficial effect of the edible coating.